Repeated sublethal freshwater exposures reduce the amoebic gill disease parasite, Neoparamoeba perurans, on Atlantic salmon. Issue 9 (25th June 2018) - Wright, Daniel William; Nowak, Barbara; Oppedal, Frode; Crosbie, Phil; Stien, Lars Helge; Dempster, Tim
Abstract: Freshwater bathing is one of the main treatment options available against amoebic gill disease (AGD) affecting multiple fish hosts in mariculture systems. Prevailing freshwater treatments are designed to be long enough to kill Neoparamoeba perurans, the ectoparasite causing AGD, which may select for freshwater tolerance. Here, we tested whether using shorter, sublethal freshwater treatment durations are a viable alternative to lethal ones for N. perurans (2–4 hr). Under in vitro conditions, gill‐isolated N. perurans attached to plastic substrate in sea water lifted off after ≥2 min in freshwater, but survival was not impacted until 60 min. In an in vivo experiment, AGD‐affected Atlantic salmon Salmo salar subjected daily to 30 min (sublethal to N. perurans ) and 120 min (lethal to N. perurans ) freshwater treatments for 6 days consistently reduced N. perurans cell numbers on gills (based on qPCR analysis) compared to daily 3 min freshwater or seawater treatments for 6 days. Our results suggest that targeting cell detachment rather than cell death with repeated freshwater treatments of shorter duration than typical baths could be used in AGD management. However, the consequences of modifying the intensity of freshwater treatment regimes on freshwater tolerance evolution in N. perurans populations require careful consideration.